Overview Of a Hospital Management Information System Using The Hot-Fit Method in Medan Hospitals in 2025 - Laia, Grace Putri; Gaol, Hotmarina Lumban; Boris, Jev (UI Scholars Hub, 2025)
Hospital Management Information System (SIMRS/HMIS) is crucial in ensuring efficiency and quality in hospital services by integrating clinical and administrative functions. This study aims to evaluate the implementation of HMIS at Medan Adventist Hospital in 2025 using the Human-Organization-Technology Fit (HOT-Fit) framework. A descriptive design with total sampling was employed, involving 70 respondents comprising medical records staff, inpatient and outpatient registration staff, and ward officers. Data were collected through a structured questionnaire adapted from a validated instrument (validity 0.690–0.900; reliability 0.841–0.911) and analyzed using descriptive statistics. The results showed a high level of implementation in all HOT-Fit domains: system use (85.7%), user satisfaction (84.3%), organizational structure (82.9%), organizational environment (87.1%), system quality (92.9%), information quality (91.4%), service quality (90.0%), and net benefit (87.1%). These findings indicate that HMIS has improved efficiency, coordination, and service quality at Medan Adventist Hospital. However, challenges remain, such as incomplete data entry, occasional system downtime, and limited IT support. Continuous improvement through training, infrastructure strengthening, and organizational commitment is needed to ensure the continued benefits of HMIS.